Ford Exposition Building (Western Publishing & Novelty Company)
The Ford Exposition Building predominates the southern promontory at Balboa Park, San Diego, where it is located in a natural spot of beauty with the Firestone Singing Fountain in the foreground. To the left is the Ford Music Bowl where symphonic, choral, and organ music are presented for the enjoyment of visitors.